Dopamine D2 and D3 receptors are linked to the actin cytoskeleton via interaction with filamin A - Lin, Ridwan (The National Academy of Sciences, 2001)
We have used a yeast two-hybrid approach to uncover protein interactions involving the D2-like subfamily of dopamine receptors. Using the third intracellular loop of the D2S and D3 dopamine receptors as bait to screen a human brain cDNA library, we identified filamin A (FLN-A) as a protein that interacts with both the D2 and D3 subtypes. The interaction with FLN-A was specific for the D2 and D3 receptors and was independently confirmed in pull-down and coimmunoprecipitation experiments. Deletion mapping localized the dopamine receptor–FLN-A interaction to the N-terminal segment of the D2 and D3 dopamine receptors and to repeat 19 of FLN-A. In cultures of dissociated rat striatum, FLN-A and D2 receptors colocalized throughout neuronal somata and processes as well as in astrocytes. Expression of D2 dopamine receptors in FLN-A-deficient M2 melanoma cells resulted in predominant intracellular localization of the D2 receptors, whereas in FLN-A-reconstituted cells, the D2 receptor was predominantly localized at the plasma membrane. These results suggest that FLN-A may be required for proper cell surface expression of the D2 dopamine receptors. Association of D2 and D3 dopamine receptors with FLN-A provides a mechanism whereby specific dopamine receptor subtypes may be functionally linked to downstream signaling components via the actin cytoskeleton.